Unlawful Acts Committed by a Notary in Form of Not Completing the Mortgage Process - Panji Rizki Gumilar; Amin Purnawan; akhmad Khisni (Sultan Agung Notary Law Review, 2021)
Public trust in the notary is the public's trust in the authentic deed he made, which is why the position of a notary is often also called the position of trust. Notaries as public officials are required to be responsible for the authentic deeds that they have made. A notary as a public official is required to be responsible for the authentic deed he has made. This is contained in UUJN no. 30 of 2004 concerning the position of a notary. The objectives of this study are as follows, one to identify and analyze the roles and responsibilities of a notary in a credit binding agreement, second to find out and analyze legal sanctions for a notary who does not complete the mortgage process and the study certificate process at the Central Artha People's Credit Bank, Brebes branch. . The approach method in this research is descriptive, which is carried out with a normative juridical approach. The type of research data used is secondary data consisting of primary legal materials and secondary legal materials. Analysis Data obtained from research results in the form of library research data (secondary) are analyzed qualitatively, the results of this study Notaries are public officials authorized to make authentic deeds insofar as the making of certain authentic deeds is not reserved for other public officials. Making authentic deeds is required by laws and regulations in order to create certainty, order, and legal protection. In addition to an authentic deed made by or before a Notary, not only because it is required by laws and regulations, but also because it is desired by interested parties to ensure the rights and obligations of the parties for the sake of certainty, order, and legal protection for interested parties at the same time for society as a whole.